ANALISIS Insider Ownership, Kebijakan Hutang dan Kebijakan Pembayaran Deviden SERTA PENGARUHNYA Terhadap Return Saham - Hermun Ningsih (Jurnal Ekonomi dan Bisnis, 2009)
The research tries to know impact insider ownership and Debt Policy to stock return. Theresearch objects are the company that was registered in the Indonesian Stock Exchange in2005 until 2008 that announce dividend. The sampling method is purposive sampling methodand it can find 13 sample companies that announce dividend. Hypothetical testing methodis Multistage Regression with the significance level 0,05. The results shows there is no significantimpact insider ownership and Debt Policy to Devidend Policy. So Devidend Policy noimpact to Stock Return.Keywords : Insider Ownership, Dividend Policy, Debt Policy, Return Saham